2002
DOI: 10.1042/bj3630329
|View full text |Cite
|
Sign up to set email alerts
|

The reassembling process of the nonameric Mycobacterium tuberculosis small heat-shock protein Hsp16.3 occurs via a stepwise mechanism

Abstract: Conditions are reported under which the reassembled intermediates of the heat-shock protein Hsp16.3 after being denatured in 8M urea were detected by mainly using urea-gradient PAGE (with modifications) and urea-denaturing pore-gradient PAGE. Hsp16.3 is the small heat-shock protein from Mycobacterium tuberculosis, which exists as a specific nonamer and was proposed to form a trimer-of-trimers structure. The refolding and reassembling of this protein was achieved rapidly by dilution or dialysis, suggesting an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Small heat shock proteins usually exist as oligomers of variable sizes, ranging from 150 kDa to 800 kDa, with each subunit being 12–42 kDa, and appear to undergo dynamic dissociation/reassociation, with oligomeric dissociation being a prerequisite for their chaperone activities [ 31 ]. sHsp16.3 of M. tuberculosis is reported to form nonamers, which are assembled and reassembled via trimer and hexamer intermediates [ 16 , 32 ]. Native form of this protein was not found to be essential for chaperone activity of the protein [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small heat shock proteins usually exist as oligomers of variable sizes, ranging from 150 kDa to 800 kDa, with each subunit being 12–42 kDa, and appear to undergo dynamic dissociation/reassociation, with oligomeric dissociation being a prerequisite for their chaperone activities [ 31 ]. sHsp16.3 of M. tuberculosis is reported to form nonamers, which are assembled and reassembled via trimer and hexamer intermediates [ 16 , 32 ]. Native form of this protein was not found to be essential for chaperone activity of the protein [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that Hsp16.3 [12,29,37] as well as other molecular chaper ones [38] are able to refold and reassemble after thermal ly or chemically induced denaturation with high efficien cy, and such a property was partially attributed to their high conformation flexibility [28,32]. The observations on the structural characteristics of the G59W mutant pro tein raise a question of whether such a structure disturbed Hsp16.3 protein will still retain its powerful ability to reassemble.…”
Section: Substitution Of the Gly59 Residue Of The Hsp163 Pro Tein Wimentioning
confidence: 99%
“…Transverse urea gradient PAGE ( Figure 3) was performed according to methods described in our previous report [11] . Urea of 6 mol/L concentration was also added in the stacking gel (4% acrylamide, pH 6.8) such that the structure of the disassembly intermediates was maintained.…”
Section: Gel Electrophoresismentioning
confidence: 99%